2019
DOI: 10.1021/acs.jafc.9b03039
|View full text |Cite
|
Sign up to set email alerts
|

3,3′-Diindolylmethane Improves Intestinal Permeability Dysfunction in Cultured Human Intestinal Cells and the Model Animal Caenorhabditis elegans

Abstract: 3,3′-Diindolylmethane (DIM), a digestive metabolite originating from cruciferous vegetables, has dietary potential for the treatment of various human intestinal diseases. Although intestinal permeability dysfunction is closely related to the initiation and progression of human intestinal inflammatory diseases (IBDs), the effect of DIM on intestinal permeability is unclear. We evaluated the effect of DIM on the intestinal permeability of human intestinal cell monolayers and the animal model Caenorhabditis elega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 50 publications
(97 reference statements)
0
18
0
Order By: Relevance
“…We found a clear difference based on microscopic observation after C. elegans was fed APDT-treated and live P. aeruginosa PAO1 for 48 h. After 3 h of staining, we observed that most infected worms absorbed the dye, as their gut was damaged, with deep blue staining, as seen in Figure 9C. Conversely, APDT P. aeruginosa-fed worms showed little staining or blue color in the body, indicating that their gut was [36]. To clearly understand the infection model, we used Brilliant Blue FCF dye, which facilitates the evaluation of gut permeability during infection by P. aeruginosa PAO1.…”
Section: Apdt Rescued Intestinal Permeability Dysfunction In C Elegansmentioning
confidence: 85%
See 4 more Smart Citations
“…We found a clear difference based on microscopic observation after C. elegans was fed APDT-treated and live P. aeruginosa PAO1 for 48 h. After 3 h of staining, we observed that most infected worms absorbed the dye, as their gut was damaged, with deep blue staining, as seen in Figure 9C. Conversely, APDT P. aeruginosa-fed worms showed little staining or blue color in the body, indicating that their gut was [36]. To clearly understand the infection model, we used Brilliant Blue FCF dye, which facilitates the evaluation of gut permeability during infection by P. aeruginosa PAO1.…”
Section: Apdt Rescued Intestinal Permeability Dysfunction In C Elegansmentioning
confidence: 85%
“…The intestinal permeability of C. elegans was measured because bacterial toxicity can be clearly observed in this nematode model, especially in the case of P. aeruginosa PAO1-infected worms, where high toxicity leads to intestinal permeability dysfunction [36]. Age-synchronized L4 worms were treated with E. coli OP50, live P. aeruginosa PAO1, or APDT-treated P. aeruginosa PAO1 for 48 h at 20 • C. The treated worms were transferred to 96-well plates containing 100 µL of Brilliant Blue FCF and incubated for 3 h at 20 • C. The Brilliant Blue FCF was mixed with an E. coli OP50 culture to a concentration of 5% w/v.…”
Section: Confirmation Of Apdt In C Elegans By Measuring Intestinal Pmentioning
confidence: 99%
See 3 more Smart Citations